Application Of Conference Writing Methods Can Improve Short Story Writing Skills - Kasmidawati Kasmidawati (Fakultas Sastra Universitas Ekasakti, 2018)
To learn something well, we need to hear, see, ask questions about it, and discuss it with others. Not only that, teachers need to